Pelatihan Konfigurasi dan Penggunaan Printer Wireless bagi Karyawan Dinas Lingkungan Hidup dan Kehutanan Provinsi Bengkulu - M. Dhaffa Ghiffari; Ardi Wijaya; M. Gilang Ramadhan; M. Sapta Firdaus (JURNAL ABDIMAS SERAWAI, 2022)
Office activities that take place almost every day, employees cannot be separated from activities that consist of correspondence to document archiving. This of course involves the use of printer equipment with a fairly high intensity. The high use of these devices is not matched by high efficiency as well. Although the printer in question already has a wireless printing feature, this function has not been utilized by employees because of the lack of information. Therefore, by doing community service (PKM) at the Environment and Forestry Service, to provide training on configuration and how to use wireless printers correctly. The training lasted for one day which was attended by employees accompanied by a trial at the end of the activity. This training is provided with the aim of empowering employees and utilizing available technology at the Community Service (PKM) implementation site. We hope that this training will have a significant impact on more efficient office activities for employees in the future.